2017
DOI: 10.1177/1687814017732676
|View full text |Cite
|
Sign up to set email alerts
|

Wayside acoustic fault diagnosis of train wheel bearing based on Doppler effect correction and fault-relevant information enhancement

Abstract: Health monitoring of train bearing is crucial to railway transport safety. More and more attention has elicited by the wayside acoustic monitoring technique in recent years than other defect detection techniques. However, wayside acoustic signal contains serious Doppler distortion and heavy background noise because of the high speed of trains. Thus, extracting fault-relevant information is difficult. A novel method for Doppler effect correction is proposed in this study by incorporating the traditional time-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Plenty of efforts; time domain and frequency energy statistics [24], using low pass filtering and Title root mean square of the signal with appropriate time windows and applying Fourier transform afterwards [25] have been given but argued to be less efficient than vibration signals [26]. However, acoustic wayside application is reported to be inefficient when Doppler correction is employed before STFT -Short Time Fourier Transform like approaches [27]. Vibration sensors (accelerometers) can also be used in the diagnosis of wheel defects efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of efforts; time domain and frequency energy statistics [24], using low pass filtering and Title root mean square of the signal with appropriate time windows and applying Fourier transform afterwards [25] have been given but argued to be less efficient than vibration signals [26]. However, acoustic wayside application is reported to be inefficient when Doppler correction is employed before STFT -Short Time Fourier Transform like approaches [27]. Vibration sensors (accelerometers) can also be used in the diagnosis of wheel defects efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative methods integrating microphone arrays and matching tracking algorithms also help to achieve similar results [122]. Liu et al combined traditional time-domain interpolation with kinematic parameter estimation and proposed an iterative algorithm based on least-squares theory [123]. They indicated that the interval between the microphone array and the middle of the track should be maintained steady to reduce the amount of calculation of additional parameters.…”
Section: Fault Diagnosis Of Wayside Acoustic Features On Train Bearingsmentioning
confidence: 99%
“…The resampled time series is obtained by re-interpolating the faulty sound source's time series T i received by the acquisition device [29]. Interpolating and resampling a Doppler-distorted signal involves correcting the nonlinear variation in the acquired acoustic signal's time series to a linear variation.…”
Section: Time Correctionmentioning
confidence: 99%